Scientific Research Training for Teachers in Bengkulu City - Connie Connie; Muhammad Kristiawan; Septi Emilya (Yayasan Sembilan Pemuda Indonesia, 2026)
Scientific research training for teachers aims to improve the professional competence of educators in carrying out educational research, especially Classroom Action Research. Research is a reflective tool that allows teachers to improve the learning process in an ongoing manner. However, many teachers face obstacles in understanding research methodologies, compiling proposals, and writing scientific reports. Therefore, community service activities are needed in the form of educational and participatory training. This activity is carried out through an andragogy approach and an experiential learning model that prioritizes the active involvement of participants. The training method consists of material presentations, discussions, workshops, and assistance in preparing research proposals. Evaluation is carried out through pre-test, post-test, and product assessment in the form of draft proposals. The output of the activity includes increasing research understanding, the ability to prepare proposals, and the growth of a research culture in the teacher environment. With this training, teachers are expected to be more confident to conduct research based on real problems in the classroom, as well as be able to produce relevant and publishable scientific works, so as to directly contribute to improving the quality of learning and teacher professionalism.